Does the tertiary health care for Type 2 diabetic patients can help to Meet the recommended glycemic targets - AL-Auqbi, Tawfeeq F. R.; AL-Sabbagh, Ahmed A. A.; Shaker, Aufaira; Al-Khalidy, Noor tha’ir Tahir (AL-Kindy College Medical Journal, 2012)
Objectives: To study the effect of providing tertiary (specialized) health care for type 2 diabetic patients to meet the WHO and ADA standards and glycemic targets. Method: Six months, Jan. – Jun. 2010, cohort study was conducted on 600 adult diabetics who registered in the National Diabetes Center (NDC) / Al-Mustansiriya University, Baghdad – Iraq. They were followed for 3- 6 months; each time patients were examined physically and their blood pressure, height, weight and BMI were measured. Fasting blood samples were taken from all patients to test the FPG, HbA1c, T.Chol, TG, HDL and LDL. Results: Patients’ age was 52.85±15.56 year and the male/female ratio was 1.01, the median duration of disease was 7 years and their BMI was 28.80 ± 13.02 kg/m2. Patients’ achievement during study period, of glycemic and cardiovascular risk factors, meet the targets of ADA, NHANES and NCEP/ATP III Guidelines of FPG, PPG, HbA1c, T.Chol, TG, LDL, HDL, systolic and diastolic blood pressure by 26.74%, 29.09%, 32.78%, 61.0%, 60.86%, 76.19%, 74.35%, 52.54% and 62.50% respectively. Conclusions: We concluded that tertiary health service can help to meet the international guidelines and recommended targets for type 2 diabetes. Improving quality and coverage of tertiary health services may help in achieve and sustain targets; and afterward close adhering to the WHO and ADA standards and glycemic targets. Abbreviations: BMI=Body Mass Index, FPG= Fasting Plasma Glucose, PPG = post prandial plasma glucose, HbA1c =glycated hemoglobin, T.Chol. = total cholesterol, TG = Triglyceride, LDL = low-density lipoprotein, HDL = high-density lipoprotein, ADA= American Diabetes Association, NHANES = National Health and Nutrition Examination Survey, NCEP/ATP III = National Cholesterol Education Program/Adult Treatment Panel